REFORMASI PENOLOGI: URGENSI PENEMPATAN DAN PEMBINAAN BAGI NARAPIDANA TRANSGENDER DI INDONESIA - Niken Subekti Budi Utami (Mimbar Hukum, 2023)
Abstract The emergence of the phenomenon of transgender people in Indonesia as a criminal subject raises the question of how to treat the law enforcement process until a transgender person becomes an inmate. This research aims to determine the placement and the coaching system of transgender inmates based on the current Correctional System (ius operatum) and formulate an Ius Contituendum for transgender inmates. This research is a normative legal study that is supported by the interview of the source. Data and documents obtained from literature research are analyzed descriptively qualitatively. The results show that the current placement and the inmate development system of transgender inmates refer to the prevailing correctional system, so they are not placed in special cells nor treated with a specific transgender inmate development system. The correctional system essentially has a soft law that accommodates the guaranteed legal protection and fulfillment of the rights of transgender inmates. Furthermore, the direction of legal development in the correctional system and criminal law has adhered to the principle of criminal individualization that focuses on the process of inmate development and mentoring according to the individual characteristics of each inmate. Therefore, ius constituendum for transgender inmates is the establishment of a specific cell that separates transgender inmates from male and female inmates, as well as a specific inmate development pattern given according to transgender inmates’ needs for them to be rehabilitated. Abstrak Munculnya fenomena transgender di Indonesia sebagai pelaku tindak pidana menimbulkan suatu pertanyaan bagaimana perlakuan dalam proses penegakan hukum hingga seorang transgender menjadi narapidana. Penelitian ini bertujuan untuk mengetahui penempatan dan pembinaan narapidana transgender berdasarkan Sistem Pemasyarakatan saat ini (ius operatum) dan merumuskan Ius Constituendum bagi narapidana transgender. Penelitian ini merupakan penelitian hukum normatif yang diperkuat dengan wawancara narasumber. Data yang diperoleh dari penelitian kepustakaan dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa saat ini penempatan dan pembinaan narapidana transgender mengacu pada sistem pemasyarakatan yang berlaku, sehingga tidak ada penempatan pada sel khusus maupun pembinaan khusus bagi narapidana transgender. Sistem pemasyarakatan pada hakikatnya telah memiliki softlaw yang mengakomodasi jaminan perlindungan hukum dan pemenuhan hak-hak narapidana transgender secara khusus. Selain itu, arah pembangunan hukum dalam sistem pemasyarakatan dan hukum pidana mengacu pada konsep individualisasi pidana yang menitikberatkan pada proses pembinaan dan pembimbingan sesuai karakteristik individu narapidana. Oleh karena itu, ius constituendum bagi narapidana transgender ialah dibentuknya sel khusus yang memisahkan narapidana transgender dari narapidana laki-laki dan perempuan, serta pola pembinaan khusus yang diberikan sesuai kebutuhan narapidana transgender sehingga mereka dapat direhabilitasi.